2018
DOI: 10.1039/c8ta01805g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cu(ii) and its selective reduction to Cu(i) within confined spaces: efficient active sites for CO adsorption

Abstract: A two-step double-solvent strategy was first used to incorporate Cu(i) sites into MIL-101(Cr), which obviously improves the CO adsorption performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…The captured CO in [EimH][OAc]–0.6CuOAc had the large red shift higher than free CO with the vibrational frequency of 2143 cm −1 and [EimH][OAc]–0.6CuOAc would have a strong chemical interaction for CO capture, making a good agreement with the previous literature reported by Wu et al 13 Therefore, it is demonstrated that the Cu + sites of [Cu(OAc) 2 ] − in ILs absorbents can preferentially capture CO through π‐complexation interaction. This π‐complexation interaction has also been employed for the capture of CO by various Cu + ‐containing solid adsorbents 31,32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The captured CO in [EimH][OAc]–0.6CuOAc had the large red shift higher than free CO with the vibrational frequency of 2143 cm −1 and [EimH][OAc]–0.6CuOAc would have a strong chemical interaction for CO capture, making a good agreement with the previous literature reported by Wu et al 13 Therefore, it is demonstrated that the Cu + sites of [Cu(OAc) 2 ] − in ILs absorbents can preferentially capture CO through π‐complexation interaction. This π‐complexation interaction has also been employed for the capture of CO by various Cu + ‐containing solid adsorbents 31,32 …”
Section: Resultsmentioning
confidence: 99%
“…for the capture of CO by various Cu + -containing solid adsorbents. 31,32 To further disclose the interaction of the anion [Cu(OAc…”
Section: Co Absorption Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…x AgM-DS was prepared by a promising DS method with some refinements. , First, 0.1 g of MIL-101 was dispersed in 20 mL of hydrophobic n -hexane to generate a suspension followed by sonicating for 15 min and stirring for 2 h. Then, 140 μL of AgNO 3 solution was added with a uniform speed in 15 min under vigorous stirring. The suspension was additionally stirred for 2 h, filtrated, and evacuated at 40 °C until dry.…”
Section: Methodsmentioning
confidence: 99%
“…A similar method was used to obtain CoMg-LDO(N) and CoMg-LDO, although an appropriate amount of Mg(NO3)2•6H2O was added [19]. CoMg-LDO(N) and CoMg-LDO were prepared to obtain a type of contrast material with larger area [20,21]. A transition metal with multiple valence states exhibits better catalytic abilities, while the Mg element is considered to be inactive.…”
Section: Synthesis Proceduresmentioning
confidence: 99%